A novel phased array antenna system for microwave-assisted organic syntheses under waveguideless and applicatorless setup conditions. Issue 115 (6th December 2016) - Horikoshi, Satoshi; Yamazaki, Satoshi; Narita, Atsushi; Mitani, Tomohiko; Shinohara, Naoki; Serpone, Nick
Abstract : An experimental microwave phased array antenna system to carry out organic syntheses and materials processing under waveguideless and applicatorless conditions is reported. Abstract : A novel phased array antenna system was tested for use in microwave-assisted organic syntheses under waveguideless and applicatorless setup conditions with the synthesis of the ionic liquid 1-butyl-3-methylimidazolium chloride ([BMIM]Cl) as an example; 5.8 GHz microwaves were used to irradiate the sample through free space a distance of 5 m from the antenna system.